2002
DOI: 10.1046/j.1439-0450.2002.00548.x
|View full text |Cite
|
Sign up to set email alerts
|

In VitroAntimicrobial Susceptibility of 183Pseudomonas aeruginosaStrains Isolated from Dogs to Selected Antipseudomonal Agents

Abstract: During the years from 1993 to 2000, 183 strains of Pseudomonas aeruginosa were isolated from different pathological specimens originating from dogs. Antimicrobial susceptibility patterns against 10 antipseudomonal agents were obtained on 183 P. aeruginosa strains. In vitro antimicrobial susceptibility testing was performed using the disk diffusion method (Kirby-Bauer). Antimicrobial susceptibility profiles showed that among beta-lactam antibiotics, imipenem was the most active compound. Out of the 183 strains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
3
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 21 publications
6
30
3
1
Order By: Relevance
“…isolated from chronic otitis externa cases in dogs. The 83.1% of 183 P. aeruginosa strains were found susceptible to gentamicin [11]. In our study 89.7% of the isolates were susceptible to gentamicin.…”
Section: Discussionsupporting
confidence: 41%
See 2 more Smart Citations
“…isolated from chronic otitis externa cases in dogs. The 83.1% of 183 P. aeruginosa strains were found susceptible to gentamicin [11]. In our study 89.7% of the isolates were susceptible to gentamicin.…”
Section: Discussionsupporting
confidence: 41%
“…isolated from dogs was proven [10]. 183 P. aeruginosa strains isolated from the outer ear canal of dogs were investigated and they found that 93.4% were sensitive to marbofl oxacin [11]. 26.1% resistance ratio was reported [1] in P. aeruginosa strains isolated from otitis cases in dogs and cats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spencer (1996) found that 95% of isolates were sensitive to ceftazidime, Panayotis et al (1998) reported 15% isolate resistance, Shawar et al (1999) 11.1%, Mueller-Premru and Gubina (2000) 9.1%, and De Champs et al (2002) 6%. In contrast, Seol et al (2002) found that 19.7% of P. aeruginosa isolated from canines was resistant to ceftazidime. The present study revealed that resistance to ceftazidime was 38.8% (17/49) for human isolates and 23.5% (4/17) for canine isolates.…”
Section: Resultsmentioning
confidence: 88%
“…Resistance to ciprofloxacin has not significantly changed since the first study was conducted in Croatia in 2002, when 93.4% of isolates were susceptible and 3.8% were resistant to ciprofloxacin (ŠEOL et al, 2002). The resistance rate reported in the Croatian study from 2011 (MEKIĆ et al, 2011) was higher (8.7%) but the main reason for that was the difference in the origin of the isolates.…”
Section: Discussionmentioning
confidence: 98%